1992
DOI: 10.1128/mcb.12.3.1292
|View full text |Cite
|
Sign up to set email alerts
|

Two alternative pathways of double-strand break repair that are kinetically separable and independently modulated.

Abstract: HO endonuclease-induced double-strand breaks in Saccharomyces cerevisiae can undergo recombination by two distinct and competing pathways. In a plasmid containing a direct repeat, in which one repeat is interrupted by an HO endonuclease cut site, gap repair yields gene conversions while single-strand annealing produces deletions. Consistent with predictions of the single-strand annealing mechanism, deletion formation is not accompanied by the formation of a reciprocal recombination product. Deletions are delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
254
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(269 citation statements)
references
References 64 publications
(85 reference statements)
14
254
0
1
Order By: Relevance
“…We hypothesized that break resection would normally be chased and terminated by DNA re‐synthesis which would have a much faster rate than the processing [140 kb/h for conventional replication (Raghuraman et al , 2001), but could be slower during repair synthesis, vs. 4 kb/h for resection (Fishman‐Lobell et al , 1992)]. In fact, by comparing the reconstitution of fragments S2 and L (Fig 6B), we could estimate the rate of dsDNA restoration in srs2 Δ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that break resection would normally be chased and terminated by DNA re‐synthesis which would have a much faster rate than the processing [140 kb/h for conventional replication (Raghuraman et al , 2001), but could be slower during repair synthesis, vs. 4 kb/h for resection (Fishman‐Lobell et al , 1992)]. In fact, by comparing the reconstitution of fragments S2 and L (Fig 6B), we could estimate the rate of dsDNA restoration in srs2 Δ.…”
Section: Resultsmentioning
confidence: 99%
“…During HR and BIR, Rad52/51/55/57 promote homology search and invasion of intact donor dsDNA by the processed broken end to initiate repair (Anand et al , 2013; Symington et al , 2014). In contrast, SSA does not require DNA external to the broken chromosome as homologous sequences on either side of the break provide complementarity between the processed ends and Rad52, but not Rad51/55/57, catalyse the strand annealing (Fishman‐Lobell et al , 1992; Ivanov et al , 1996). …”
Section: Introductionmentioning
confidence: 99%
“…Previous work in young cells has demonstrated that different repair pathways can compete for the same DNA lesion (Fishman-Lobell et al, 1992). In effect the DNA end produced at a DSB site is a substrate for which various DNA repair proteins compete.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sister chromatid exchange cannot take place in G1 (there is no sister chromatid). In fact, homologous recombination appears to be repressed in G1 (Fishman-Lobell et al, 1992) and NHEJ is preferentially used in this stage of the cell cycle (Aylon and Kupiec, 2005). Cell-type specific regulation of the DNA damage repair method has also been demonstrated.…”
Section: Unresolved Issuesmentioning
confidence: 99%
See 1 more Smart Citation